Adhering to lifestyle change recommendations via the trans-theoretical model: a mixed-methods study among type 2 diabetes patients - Mohamed Nor, Noraishah; Sidek, Suriati; Saad, Nurulwahida; Jaafar, Nurul Hazirah; Mohd Shukri, Nor Azwani (Emerald Publishing Limited, 2020)
Purpose – This paper aims to identify and explore the factors affecting type 2 diabetes mellitus (T2DM) patients’ adherence to lifestyle change recommendations, with the guidance of the trans-theoretical model (stages of change). Design/methodology/approach – This study was conducted in two parts. In Part A, 163 randomly selected participants were asked to complete a cross-sectional survey. Data regarding demographics, stages of change and levels of confidence to engage in lifestyle changes were collected. In Part B, in-depth interviews were conducted among 30 individuals, aged between 30 and 65 years, had been diagnosed with T2DM and had seen dietitian at least once. Purposive sampling was used to recruit participants with different sociodemographic characteristics. Findings – Part A showed that most of the participants were in the pre-action group (60%), with a higher mean HbA1c (8.9%) as compared to the action group (40%) which had a mean HbA1c of 6.9%. Part B further revealed the pre-action group and action group identified four key themes concerning lifestyle changes adherence: stumbling block; self-care belief; knowledge implementation; and self empowerment. Practical implications – Health-care providers should identify patients’ stages of change before lifestyle changes implementation. Originality/value – This study highlighted that many factors might influence a T2DM patient’s adherence to lifestyle change recommendations. Determining the stages of change and self-confidence of T2DMpatients is needed to ascertain long-term adherence.